Differentiation of mesenchymal stem cells -derived trabecular meshwork into dopaminergic neuron-like cells on nanofibrous scaffolds. (November 2017) - Jamali, Simin; Mostafavi, Hossein; Barati, Ghasem; Eskandari, Mehdi; Nadri, Samad
Abstract: Parkinson's disease (PD) is a neurodegenerative disorder of the brain which is produced by the damage to dopaminergic neurons. Stem cell transplantation with a nanofibrous scaffold is one of the encouraging strategies for Parkinson's disease therapy. In this study, human mesenchymal stem cells (MSCs) from eye trabecular meshwork (TM) were differentiated into dopaminergic neurons on nanofibrous scaffold. After Trabecular meshwork biopsy, MSCs were isolated, cultivated on Poly-l -Lactide Acid (PLLA) nanofibrous scaffold (fabricated by electrospinning methods) and treated with medium containing DMEM supplemented with RA, IBMX and forskolin for 7 days. Scanning electron microscopy imaging, qPCR and immunostaining were used to analyze differentiated TM-MSCs on scaffold and their expression of dopaminergic-specific markers such as TH and Nurr-1. qPCR analysis revealed the expression of dopaminergic neuron genes such as TH, Nurr-1 on fibrous scaffold as well as TCPS. Immunostaining revealed that the differentiated TM-MSCs on TCPS and Scaffold not only express TH and Nurr-1 genes, but also express TH protein. In conclusion, the results indicate that TM-MSCs might be a suitable source for cell transplantation therapy. In addition the nanofibrous scaffold reported herein could be used as a potential cell carrier for the central system diseases such as PD.